Reconstrução da matriz densidade via corrente spin polarizada - Sambú, Midana Baial (2023)
This present thesis araised as theorical proposal for the reconstruction of density matrix of a single electron spin qubit using spin polarized transport. This model consists in a composed system for quantum dot attached to the ferromagnetics reservoir with magnetic field along plane on the Bloch sphere. The aim is investigating tunneling events of polarized spin along ±, ± and ± direction that provide distribuition of probabilities along these axis-quantization, in which we relate, through Stokes parameters, with density matrix, allowing, thereby, the reconstruction of the density matrix. For this aim, we did experimental simulation using python in which we created code that allowed us making the simulation of the system. Being an open system, we used the Lindblad master equation to simulate the dynamics of the system that provide us the evolution of the system along time. After experimental simulation, we were able of reconstructing the density matrix from probabilities getting through of dynamics of the system, verifying, thereby, the predict results by our theorical model. The model offers a vision about density matrix of open quantum system, probability amplitudes and relative phases.